Intuitive intelligence in business: introduction - Subiah, Manj (Henry Stewart Talks, 2019)
Evolutionary intelligence, Volatility, uncertainty, complexity, ambiguity (VUCA), Business context, Stakeholders, Types of intelligence, Conscious and unconscious decision making, Filters, Self-assessment